The Effect of Carbimazole Following Radioiodine Therapy on Radiation Dose to the Thyroid - Gimlette, T.M.D.; Kocak, R.; Herbert, R.G.; Squire, C.R. (Nuklearmedizin - NuclearMedicine, 1981)
Radioiodine in the thyroid gland after a therapy dose of 131I was measured serially in 7 patients without Carbimazole, and in 11 patients starting Carbimazole 60 mg daily fourteen days after the therapy dose. Effective half-life for radioiodine in the gland initially 5.53±1.08 days fell to 4.26±1.12 days (p < 0.01) during Carbimazole, and returned to 5.83±1.21 days (NS) after stopping the drug. The radiation dose to the thyroid from a given therapy dose of 131I followed by Carbimazole was calculated to be 97% of that without Carbimazole when the drug was started after 14 days, and 90% and 75% when the drug was started after 7 days and 1 day respectively.